The Use of AI In Strategic Management: A Qualitative Study - Maciej CIOLEK (Communications of International Proceedings, 2025)
The aim of this study is to investigate how artificial intelligence (AI) can revolutionize strategic management and its fundamental procedures. A thorough examination of AI's advantages, difficulties, and potential effects on strategic decision-making is lacking in literature, despite the field's notable advances. By analyzing the development and integration of AI in strategy creation, assessment, and adaptation, this paper fills this gap. To evaluate AI's contribution to improving foresight, scenario planning, and competitive agility, the study uses a qualitative approach, analyzing most recent literature, industry reports and tech companies reports. The study also examines past advancements in the application of analytics and decision-support tools in strategic management before artificial intelligence. The results show that by automating environmental scanning, risk modeling, and war-gaming simulations, AI greatly increases strategic speed and foresight. Predictive analytics and dynamic capability building are two areas where AI-powered solutions shine, offering deeper insights and bolstering executive judgment. But issues like a lack of trust, an excessive dependence on data, and ethical governance still exist. With possible advancements in AI-augmented cognition, real-time strategy adaptation, and human-AI co-strategizing sets to transform the sector, the future of AI in strategic management seems bright. This thorough examination emphasizes how crucial it is to comprehend how AI affects strategic management to successfully navigate its adoption.
Keywords: artificial intelligence; strategic management; executive decision-making; human-AI collaboration